Engaging the moving image - Carroll, Noël, 1947- (Yale series in the philosophy and theory of art., 2003)
Noël Carroll, film philosopher, has gathered in this book 18 of his most recent essays on cinema and television - what Carroll calls 'moving images'. The essays discuss topics in philosophy film theory, and film criticism.